A service evaluation of an integrated model of palliative care of cystic fibrosis. (July 2016) - Bourke, Stephen J; Booth, Zoe; Doe, Simon; Anderson, Alan; Rice, Sarah; Gascoigne, Alistair; Quibell, Rachel
Background: Patients with advanced cystic fibrosis have severe symptoms with a complex trajectory of exacerbations and recovery. They are often awaiting lung transplantation, and many die without receiving specialist palliative care. Aim: We introduced an integrated model whereby palliative specialists joined the cystic fibrosis team to provide palliative care in parallel with standard care. Design: A service evaluation of this model of care was undertaken in a prospective case series documenting symptoms and outcomes, the views of the cystic fibrosis team and the experience of the palliative specialists. Setting/participants: Over 3 years, 28 (10%) of 282 patients attending the cystic fibrosis centre had specialist palliative care. Results: They had advanced lung disease (mean forced expiratory volume in 1 s (FEV1) = 0.86 L (25% predicted)), and 17 died: 6 were on a transplant waiting list at death; 10 were unsuitable and 1 died post transplantation. All who died over these 3 years had specialist palliative care. Four patients had successful transplants. Assessment showed a high prevalence of breathlessness, cough, pain, vomiting and fatigue, with a significant impact on daily life. The cystic fibrosis team rated this model of care highly, felt that palliative care should be members of the team, and thought that patients had found it helpful. The palliative specialists gained knowledge of cystic fibrosis, found it beneficial to meet patients earlier in the disease, and identified unmet needs in managing bereavement and the effects of deaths on other patients with cystic fibrosis. Conclusion: This model has been successful in overcoming the difficulties in access to specialist palliative care for patients with cystic fibrosis.